PERAN MODAL KEMAMPUAN DAN PENGETAHUAN DALAM BERWIRAUSAHA YANG MENDORONG KEBERHASILAN USAHA DI KALANGAN MAHASISWA - ramadhan, dias rafah; Alexsa, Alexsa; Anas, Maulidah Hasnah; Lubis, Muhammad Rival; Lubis, Eva Susanti (Jurnal Akuntansi, 2024)
This study aims to understand how skills and knowledge contribute to the success of students in entrepreneurship. Using a qualitative approach through in-depth interviews, the research reveals that entrepreneurial success is not solely dependent on financial capital but also on personal capital such as skills, knowledge, and determination, combined with external support like social relationships and business location. For instance, a student utilizing their cooking skills to start a small business demonstrates the importance of adaptability, perseverance, and time management. The study concludes that a combination of internal and external capital, along with a desire for continuous learning and innovation, can enhance entrepreneurial success among students.